2023
DOI: 10.1177/13694332231153976
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviors of bridges — A literature review

Abstract: This work provides a comprehensive review of previous studies concerning the static thermal behaviors of various types of bridges, including beam bridges, arch bridges, cable-stayed, and suspension bridges. Given that thermal behaviors are closely associated with the temperature distribution of bridges, the basis of the heat transfer analysis is briefly introduced first. The studies of the temperature distribution and the temperature actions of each type of bridge are then reviewed from the perspective of theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Sun et al (2018) and Shan et al (2018) have revealed the influence of temperature on the natural frequencies of bridges, considering both theoretical analysis and empirical data. Li et al (2023) argued that the temperature effects on cable-stayed bridges are complex. They advocated for exploring global 3D temperature effect numerical simulations and optimizing the placement of temperature sensors based on the boundary conditions required by the numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2018) and Shan et al (2018) have revealed the influence of temperature on the natural frequencies of bridges, considering both theoretical analysis and empirical data. Li et al (2023) argued that the temperature effects on cable-stayed bridges are complex. They advocated for exploring global 3D temperature effect numerical simulations and optimizing the placement of temperature sensors based on the boundary conditions required by the numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of research findings exist for various bridge types. Li et al (2023) conducted a comprehensive review, examining the temperature distribution and effects on different bridge types—girder, arch, cable-stayed, and suspension bridges—employing theoretical analysis, numerical simulations, experimental tests, and field monitoring. In a study by (Lee, 2016a; Lee et al, 2016), design-effective temperatures for steel box girders were estimated and evaluated using temperature field monitoring data gathered from both full-size steel box girder specimens and operational bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Exposed to ambient temperature and solar radiation, bridges are subjected to daily and seasonal thermal effects (Dai et al, 2022; Xia et al, 2022; Li et al, 2023). Variations in structural temperature are likely to induce deformations and stresses, especially for long-span cable-stayed bridges.…”
Section: Introductionmentioning
confidence: 99%